Institutional Barriers in the Coproduction of Knowledge for Transportation Planning. (19th October 2020) - Nostikasari, Dian; Casey, Colleen
ABSTRACT: Barriers to an inclusive planning process include institutional context shaped by organizational structures, interactions between professionals outside of their disciplines, and practices. We seek to understand the extent planners and modelers privilege certain types of data and knowledge in practice. The article presents a US case study of Dallas-Fort Worth, Texas, drawing from analyses of planning documents, interviews with transportation planners, modelers, and residents. We focus on the privileges given to knowledge derived from transport prediction models within an existing institutional context – over more grounded and specific experiential knowledge. We find that breaking down institutional barriers, specifically those tied to legitimacy, is a precursor to inclusion. Furthermore, tools and techniques selected in the planning process are as equally important as the participants invited to the table.